PELUANG USAHA MELALUI AGRIBISNIS MINA PADI UNTUK MENINGKATKAN PENDAPATAN PETANI - Sularno, Sularno; Jauhari, Sodiq (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
Food  is  a  commodity  that  is  very  strategic  and  always  needed  by  the community.  Therefore  the  food  supply  must  be  guaranteed  to  meet  the  needs  of  the community.  The  agricultural  sector  has  a  very  important  role  in  the  national  food supply.  Dominant contribution of  the agricultural sector  particularly  in  strengthening food security.  Respect  it is  necessary to find  a solution  to  support the  improvement  of food security  programs  geared  to meet  the food needs of  the community.  To  support the activities of the program has been carried out assessment of business opportunities through  farming  fish  rice  to  increase farmers' income.  In the implementation of  this study  by  utilizing  irrigated  land  area  of  1  hectare  for  rice  farming  and  business varieties  Sidenuk  of fish nila.  Data  type of  the data  collected  primary  and  secondary data.  To  support  the  study  used  a  SWOT  (Strenght,  Weakness,  Oppotrtunity  and Threath) analysis,  while for  the feasibility  analysis  used  R/C  ratio  and  B/C  ratio.  The study showed  that  agribusiness  fish  rice  farming  can  provide an additional  net  profit of    7,165.250  million  (35.29%),  with  the  R/C  ratio  of  2.97  and    B/C  ratio  of  1.97. Based on the assessment results, the agribusiness farming fish rice developed feasible.